IMPLEMENTASI KEBIJAKAN PERATURAN BUPATI NO 20 TAHUN 2019 TENTANG SISTEM ONLINE PAJAK DAN RETRIBUSI DAERAH DI KECAMATAN MARITENGNGAE KABUPATEN SIDENRENG RAPPANG - Ridwan Syahrir; Lukman Lukman; Madaling Madaling (JIA: Jurnal Ilmiah Administrasi, 2021)
This study aims to determine the Implementation of Regulations Policy No. 20 Regent about the online system of taxes and local levies in Sidenreng Rappang Regency. The population in this study amounted to 213 while the samples taken were 21 respondents. The sampling technique used is using the Yount formula. Data collection techniques used through observation, questionnaires, documentation. The data analysis technique used is descriptive analysis with a frequency table. The results of this study indicate that the implementation of Bupati regulation regulation no 20 2019 on the online system of regional taxes and user charges in the Maritengngae District of Sidenreng Rappang Regency is in the effective category, as the result of data processing shows the category of "Good / effective" with a percentage of 57.82%. The most influential factor is the policy disposition of 63.70%, and the lowest yield is the resource factor of 53.55%.